Exploratory Analysis of 18F-3’-deoxy-3’-fluorothymidine (18F-FLT) PET/CT-Based Radiomics for the Early Evaluation of Response to Neoadjuvant Chemotherapy in Patients With Locally Advanced Breast Cancer - Fantini, Lorenzo; Belli, Maria Luisa; Azzali, Irene; Loi, Emiliano; Bettinelli, Andrea; Feliciani, Giacomo; Mezzenga, Emilio; Fedeli, Anna; Asioli, Silvia; Paganelli, Giovanni; Sarnelli, Anna; Matteucci, Federica (Frontiers in Oncology, 2021)
Purpose. The objective of this study was to evaluate a set of radiomics-based advanced textural features extracted from 18F-FLT-PET/CT images to predict tumor response to neoadjuvant chemotherapy (NCT) in patients with locally advanced breast cancer (BC). Materials and Methods. Patients with operable (T2-T3, N0-N2, M0) or locally advanced (T4, N0-N2, M0) BC were enrolled. All patients underwent chemotherapy (6 cycles every 3 weeks). Surgery was performed within 4 weeks of the end of NCT. The MD Anderson Residual Cancer Burden calculator was used to evaluate the pathological response. 18F-FLT-PET/CT was performed 2 weeks before the start of NCT and approximately 3 weeks after the first cycle. The evaluation of PET response was based on EORTC criteria. Standard uptake value (SUV) statistics (SUVmax, SUVpeak, SUVmean), together with 148 textural features, were extracted from each lesion. Indices that are robust against contour variability (ICC test) were used as independent variables to logistically model tumor response. LASSO analysis was used for variable selection. Results. Twenty patients were included in the study. Lesions from 15 patients were evaluable and analyzed: 9 with pathological complete response (pCR) and 6 with pathological partial response (pPR). Concordance between PET response and histological examination was found in 13/15 patients. LASSO logistic modelling identified a combination of SUVmax and the textural feature index IVH_VolumeIntFract_90 as the most useful to classify PET response, and a combination of PET response, ID range and ID_Coefficient of Variation as the most useful to classify pathological response. Conclusions. Our study suggests the potential usefulness of FLT-PET for early monitoring of response to NCT. A model based on PET radiomic characteristics could have good discriminatory capacity of early response before the end of treatment.